Isthmin 1 is Expressed by Progenitor-Like Cells in the Lung: Phenotypical Analysis of Isthmin 1+ Hematopoietic Stem-Like Cells in Homeostasis and during Infection - Guadalupe Rivera-Torruco; Carolina A. Martínez-Mendiola; Tania Angeles-Floriano; Gustavo Alberto Jaimes-Ortega; José Luis Maravillas-Montero; Rodolfo García-Contreras; Yolanda González; Esmeralda Juárez; Porfirio Nava; Vianney Ortiz-Navarrete; Oscar Medina-Contreras; Paula Licona-Limón; et al. (Journal of Immunology Research)
The process by which blood cells are generated has been widely studied in homeostasis and during pathogen-triggered inflammatory response. Recently, murine lungs have been shown to be a significant source of hematopoietic progenitors in a process known as extramedullary hematopoiesis. Using multiparametric flow cytometry, we have identified mesenchymal, endothelial, and hematopoietic progenitor cells that express the secreted small protein Isthmin 1 (ISM1). Further characterization of hematopoietic progenitor cells indicated that ISM1+ Lineage- Sca-1+ c-kit+ (ISM1+ LSK) cells are enriched in short-term hematopoietic stem cells (ST-HSCs). Moreover, most Sca-1+ ISM1+ cells express the residence marker CD49a, and this correlated with their localization in the extravascular region of the lung, indicating that ISM1+ cells are lung-resident cells. We also observed that ISM1+ cells express TLR4, TLR5, and TLR9, and, in a mouse model of sepsis induced by P. aeruginosa, we observed that all the LSK and ISM1+LSK cells were affected. We conclude that ISM1 is a novel biomarker associated with progenitor-like cells. ISM1+ cells are involved in the response to a bacterial challenge, suggesting an association between ISM1-producing cells and dangerous inflammatory responses like sepsis.